Measuring the Social Impact of the Cultural and Creative Sectors: Insights from Lithuanian Experts - Kublickienė, Lilija (Information & Media, 2025)
The article discusses the challenges of social impact assessment in the Cultural and Creative Sectors (CCS) in Lithuania. The varying definitions of key concepts, such as ‘cultural and creative sectors’ and ‘impact’, have led the theoretical part of the paper to focus on the clarification of these concepts, reviewing their development and the practice of application. The importance of assessing the social impact of CCS is emphasized, alongside an exploration of diverse research and measurement practices.The empirical part of the article discusses the findings of a qualitative research with Lithuanian CCS experts and presents the conclusions drawn from it. The research aimed to explore experts’ views on the challenges of measuring the social impact of CCS. The results facilitated the identification of key factors considered essential for ensuring reliable impact measurement: conceptual clarity, accounting for sub-sectoral diversity, integrating quantitative and qualitative methods, and focusing on causal links and the long-term nature of change.
Keywords: cultural and creative sectors; cultural and creative industries; social impact